Respiratory Complications of Plasmodium vivax Malaria: Systematic Review and Meta-Analysis - Val, Fernando (Am J Trop Med Hyg, 2017)
Malaria, a major global public health problem, is mainly caused by Plasmodium falciparum and Plasmodium vivax, and is responsible for nearly half a million deaths annually. Although P. vivax malaria was not believed to cause severe disease, recent robust studies have proved otherwise. However, the clinical spectrum and pathogenesis of severe vivax malaria and, especially, its respiratory complications remain poorly understood. A systematic search for articles reporting respiratory complications associated with vivax malaria was performed in Lilacs, Cochrane, Scielo, Web of Science, and Medline databases irrespective of publication date. Prevalence of acute respiratory distress syndrome (ARDS) and associated mortality among vivax patients were calculated from cross-sectional and longitudinal studies, whereas factors associated with mortality were calculated from data pooled from case reports and series of cases. A total of 101 studies were included (49 cross-sectional or longitudinal and 52 case reports or series of cases). Prevalence of ARDS was 2.8% and 2.2% in children and adults, respectively, with nearly 50% mortality. Moreover, female sex (P = 0.013), having any comorbidity (P = 0.036), lower body temperature (P = 0.032), lower hemoglobin (P = 0.043), and oxygen saturation (P = 0.053) values were significantly associated with mortality. Plasmodium vivax malaria respiratory complications included ARDS and were associated with high mortality. Demographics and clinical characteristics upon presentation to hospital were associated with mortality among patients with respiratory complications in vivax malaria. This study reaffirms the evidence of severe and fatal complications of P. vivax malaria and its associated respiratory complications.